2022
DOI: 10.3390/fractalfract6020058
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Analytical Formula for the Discounted Moments of the ECIR Process and Interest Rate Swaps Pricing

Abstract: This paper presents an explicit formula of conditional expectation for a product of polynomial functions and the discounted characteristic function based on the Cox–Ingersoll–Ross (CIR) process. We also propose an analytical formula as well as a very efficient and accurate approach, based on the finite integration method with shifted Chebyshev polynomial, to evaluate this expectation under the Extended CIR (ECIR) process. The formulas are derived by solving the equivalent partial differential equations obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…n ] in terms of generalized hypergeometric functions. We remark that computing E[Y γ n ] relies on the c k coefficients which can be obtained from the recursive Formulas ( 4)-( 7), and we demonstrate later in our numerical study in Section 5 that implementing our Formula (8) for computing E[Y γ n ] consumes significantly less time and effort than employing MC simulations.…”
Section: Theorem 2 Essentially Expresses E[y γmentioning
confidence: 77%
See 1 more Smart Citation
“…n ] in terms of generalized hypergeometric functions. We remark that computing E[Y γ n ] relies on the c k coefficients which can be obtained from the recursive Formulas ( 4)-( 7), and we demonstrate later in our numerical study in Section 5 that implementing our Formula (8) for computing E[Y γ n ] consumes significantly less time and effort than employing MC simulations.…”
Section: Theorem 2 Essentially Expresses E[y γmentioning
confidence: 77%
“…In hypothesis testing, several test statistics converge in distribution toward a conic combination of independent noncentral chi-square random variables (see, e.g., [2][3][4][5]). Moreover, f Y n (y) and E[Y γ n ] play an interesting role in financial applications; see, e.g., [6][7][8][9][10][11]. Very recently, Rujivan and Rakwongwan [11], Chumpong et al [6], and Rujivan [10] showed that the log-return realized variance when the underlying asset follows the extended Black-Scholes model can be expressed in terms of a conic combination of independent noncentral chi-square random variables.…”
Section: Introductionmentioning
confidence: 99%
“…In the context of future works, our proposed closed-form formulas under the IND-CEV process have further beneficial aspects for pricing financial derivatives, such as moment swaps and the asset whose payoff can be generated by the conditional moments, see more details in [23,30]. In addition, since the transition PDF of process ( 2) is complicated and does not exist in closed form, our closed-form formulas can also be applied for parameter estimations of the behavior and dynamic of observed data; see more details in [9].…”
Section: Conclusion Limitations and Future Researchesmentioning
confidence: 99%
“…There are several empirical studies confirming that a mean-reverting drift process, such as the Vašíček, Ornstein-Uhlenbeck (OU) [5] and Cox-Ingersoll-Ross (CIR) [6] processes, should not necessarily be linear. Indeed, the behaviors and dynamics of interest rate and its derivatives prefer nonlinearity in the mean-reverting drift rather than linear drift processes; see for more details in [7][8][9][10]. In order to extend the OU process, a nonlinear diffusion process was introduced by Cox [11], namely, the constant elasticity of variance (CEV) process.…”
Section: Introductionmentioning
confidence: 99%
“…This method, later known as the FIM using the Chebyshev polynomial expansion (FIM-CPE), published in 2020 [3], significantly outperformed all preceding versions of FIM, marking a major leap forward in the field. There are applied to solve many problems, see [3][4][5][6][7][11][12][13][14][15][16] for more details. Nevertheless, it is important to note that extensive applications of this FIM-CPE…”
Section: Introduction 11 Motivation and Literature Surveysmentioning
confidence: 99%